Enabling energy-efficient renovation: the case of vertical extension to buildings. Issue 1 (5th March 2019) - Sundling, Rikard; Blomsterberg, Åke; Landin, Anne
Abstract : Purpose: This paper is based on a study of six similar buildings built in Gothenburg, Sweden, in 1971, which were in urgent need of renovation. A life cycle profit analysis shows how four competing concepts were evaluated to find a financially viable renovation concept; additionally, the environmental impacts of these renovation concepts using a life cycle assessment are presented. Design/methodology/approach: Four renovation concepts are compared to find the most appropriate concept, namely, minimalist, code-compliant, low-energy and low-energy plus vertical extension concepts. The methods used for comparison are life cycle profit analysis and life cycle impact assessment; the methods used for data gathering included site visits, interviews, document study, co-benefits study and energy simulation. Findings: The findings show that vertical extension supported the energy-efficient renovation of the buildings and that the combination of low-energy and the vertical extension had the highest return on investment and the lowest environmental impact. The selected concept for renovating the remaining five buildings combined was the low-energy plus vertical extension. Additional benefits from vertical extension include more apartments in central locations for the housing company, a wider variety of apartment layouts and a wider range of tenants. Drawbacks include increased use of infrastructure, green space and common appliances, as well as gentrification. Originality/value: This study shows how a vertical extension can financially enable an energy-efficient renovation and further lower its environmental impact. Benefits and drawbacks of densification are also highlighted to better understand the implementation of vertically extending a building.